Application of flexible scope in large testing laboratories - Di Candia, Carina; Flores, Laura; Trias, Monica (INNOTEC, 2011)
According as the international definition of Flexible Scope, a laboratory must demonstrate face with the accreditation body that it has the knowledge, experience and competence to work within the full range of its flexible scope, as well as possessing suitable laboratory environments and equipment. The laboratory must also demonstrate that it has a management system in place that can control its proposed approach while continuing to comply with the requirements of ISO 17025:2005. In case of UKAS (Unites Kingdom Accreditation Service), prior to offering accreditation for flexible scope they must have a high degree of confidence that the staff are technically competent and that the management system controlling certain key processes as development, review, validation and authorization. LATU apply these requirements since 2004 as "Unified Tests". Until this date, LATU was doing the same type of tests in different materials departments using different equipment, personal, and testing quality control. In order to that were defined cross disciplinary groups to analyze this topic approaching in personal competence and quality control tests improvement, and resource's decrease. For example, LATU has the Unified Test Tensile Strength accredited by UKAS in: corrugated and solid fiberboard, paper board, linerboard, cork plugs, plastic bags, plastic sheeting, paper, woven fabrics, plastic woven bags and woven plastic. As a result of the Unified Tests was generated a general unified manage procedure with unified criteria's, responsibilities and actions. Was written a unique testing procedure not only with the actual flexible scope and the flexibilities limits but also the compliance requirements of ISO 17025 and the accreditations body methodology. We could decrease the amount of documentation to control. Was defined the methodology and implemented periodicaly internal inter comparisons between departments in order to valid the unified tests and has a unique calculation method of uncertainty of measurement for tests performed in different departments. The equipment joint control allows everybody to use all the equipment, optimization resources and assurance the maintenance and calibration of them. The training together lead to the polyvalence personal.